Exploring the Potential of Chitosan-based Nanoparticles as Novel Carrier for Oral Delivery of Protein and Peptide Drugs - Ranu Biswas; Md Ahesan Ansari; Sourav Mondal; Tanima Sarkar; Pritam Kapat; Arindam Ghosh (Pharmaceutical Science: New Insights and Developments Vol. 3, 2025)
Therapeutic proteins represent an appreciable part of pharmaceuticals but oral delivery of protein via conventional methods faces barriers in permeability and stability. Polymeric nanoparticles overcome these barriers and act as nanocarriers. Chitosan is preferred as the polymer for nanoparticle formulation as it imparts advantages like biocompatible, biodegradable, and less toxic. So, this chapter explores the potential of chitosan nanoparticles as novel carriers for oral delivery of protein and peptide drugs. Chitosan-based nanoparticle shows favorable properties for the oral delivery of protein like protein encapsulation, improvement of protein stability and sustained release effect. They can be used as potential delivery carriers of protein and other pharmaceutical agents. Chitosan and modified chitosan can be used as polymers while preparing the formulation of polymeric nanoparticles via different methods ionic gelation techniques, emulsion solvent evaporation method, emulsification solvent diffusion etc. The chitosan-based nanoparticles may be used successfully for the oral delivery of therapeutic proteins. Chitosan-based nanoparticles have tremendous potential for improving protein delivery and promoting additional research and development in this field.